أثر النقل السككي السوري على نمو الصادرات السورية إلى الدول المجاورة خلال الفترة ( 2000- 2010) - محمود حبيب; حسن عادل (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يدرس هذا البحث الدور الهام الذي يمكن أن يلعبه النقل السككي السوري في تطوير التبادلات التجارية السورية مع بلدان العالم وبالأخص الدول المجاورة التي تربطنا بها شبكة من الخطوط الحديدية, وتطرح مشكلة البحث التساؤل الآتي : ما الدور والأثر الذي يمكن أن يؤديه النقل السككي في نمو الميزان التجاري وبالأخص نمو قطاع الصادرات السورية إلى بلدان العالم, حيث تركزت أهداف البحث على دراسة تطور ايرادات النقل السككي السوري خلال فترة عشر سنوات (2000-2010) ودراسة تطور الصادرات السورية عبر الزمن خلال نفس الفترة ومن ثم تمت دراسة العلاقة بين المتغيرين المذكورين وتحليلها باستخدام نظام (SPSS) وصولاً إلى تحديد العلاقة بينهما، وقد توصل الباحث إلى نتائجٍ عدةٍ ومنها: ضعف النقل السككي السوري وارتفاع تكاليفه وعدم قدرته على منافسة بقية قطاعات النقل داخل البلد وخارجه، وبالرغم من ذلك فإنه يسهم إلى حدٍ كبيرٍ في تطوير وزيادة حجم ونوع الصادرات إلى دول العالم وخاصة إلى الدول المجاورة والتي تربط سورية بها شبكة من الخطوط الحديدية، وتوصل الباحث إلى توصيات منها: زيادة تطوير شبكة الخطوط الحديدية واعتماد نظام التكاليف المعيارية وبناء المرافئ الجافة وزيادة الخطوط الحديدية وتوسيع الشبكة لتشمل معظم المناطق ومعظم دول العالم من أجل تفعيل الدور الهام الذي يمكن أن يلعبه النقل السككي في تطوير التبادلات التجارية مع معظم الدول. This research studies the important role that can be played by the railway transportation in the development of the Syrian commercial exchanges with countries around the world، especially the neighboring countries with which we have a network of railway lines, And the problem of this research leads us to ask the following question: What are the role and effect that can be played by the railway transportation in the growth of the commercial balance and especially the growth of the Syrian export sector to the countries of the world, while the aims of research concentrate on the study of the development of the Syrian railway transportation income within the period of ten years(2000-2010) and the study of the development of the Syrian exports within the same period of time then, the relationship between the previous items was studied and they were analyzed by using (SPSS) system to determine the relationship between them. The researcher reaches several results, such as the weakness of the Syrian railway transport and the highness of its costs and inability to compete with other sections of local and external transportation never the less it still contributes in the development and the enhancement of the quality and quantity of the exports to the countries around the world, especially the neighboring countries with which we have a network of railway lines, moreover the researcher has come to recommendations such as the enhancement of the development of the railway network and the adoption of standardized costs system and the increment of the railway lines, and the extension of the network to cover all areas and countries around the world for the activation of the important role that played by the railway transportation in the development of commercial exchanges with countries around the world .